2021
DOI: 10.1007/s11113-021-09642-x
|View full text |Cite
|
Sign up to set email alerts
|

Acculturation and Self-rated Health Among Asian Immigrants: The Role of Gender and Age

Abstract: Using the 2002–2003 National Latino and Asian American Study (NLAAS), we examine the relationship between acculturation and poor-to-fair self-rated health (SRH) among Asian immigrants (N = 1639). Using latent class analysis, we construct a multidimensional measure of acculturation that considers dimensions of involvement in U.S. culture as well as attachment to Asian ethnic cultures and identify three classes of Asian immigrants: the assimilated, who most strongly adhere to U.S. culture; the integrated, who al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 71 publications
0
7
0
Order By: Relevance
“…For example, acculturative stress is prominent for less acculturated Asian Americans, which contributes to poor mental health and ultimately worse SRH despite their lower prevalence of major diseases compared to more acculturated populations ( 14 ). Additionally, more acculturated Asian Americans are more likely to receive health screening and healthcare services than less acculturated Asian Americans ( 14 , 32 , 34 , 54 ). In particular, higher English proficiency and more bicultural or western identity—the acculturation factors most associated with better SRH—are likely associated with higher health literacy and better access to health care, as structural barriers to access will be easier for those individuals to overcome ( 55 57 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, acculturative stress is prominent for less acculturated Asian Americans, which contributes to poor mental health and ultimately worse SRH despite their lower prevalence of major diseases compared to more acculturated populations ( 14 ). Additionally, more acculturated Asian Americans are more likely to receive health screening and healthcare services than less acculturated Asian Americans ( 14 , 32 , 34 , 54 ). In particular, higher English proficiency and more bicultural or western identity—the acculturation factors most associated with better SRH—are likely associated with higher health literacy and better access to health care, as structural barriers to access will be easier for those individuals to overcome ( 55 57 ).…”
Section: Discussionmentioning
confidence: 99%
“…Ro and colleagues also demonstrated that SRH improved with longer duration in the U.S. particularly among older cohorts of Asian immigrants ( 28 ). A recent study reported the moderating role of age in the association between the acculturation and SRH with different patterns by gender: the probability of having poor to fair SRH increased with age among less acculturated or bicultural Asian immigrant women, whereas the probability increased steeply with age among the highly acculturated Asian immigrant men ( 34 ). Older Asian immigrants are more likely to suffer from isolation and limited utilization of health services than their younger counterparts ( 30 , 37 , 38 ) which may result in poor SRH.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is consistent with the findings of Suleiman et al (2021), who have discovered that greater heritage identity is associated with a lower risk of poor self-rated health [ 36 ]. Meanwhile, research conducted among Asian immigrant groups has found that the separated are significantly more likely than the assimilated to report poor-to-fair SRH [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, acculturation can increase stress or conflict between two competing cultures [42] or be associated with decreased social support [43]. Not surprisingly, empirical findings have been mixed, with some studies linking higher acculturation to a new culture to poorer SRH [38,39], while others show favorable relationship to mental health [37,44] or no relationship at all [36].…”
Section: Discussionmentioning
confidence: 99%